Legal system of community and its harmonization in the European Union - N I Shapovalov (RUDN Journal of Law, 2012)
The material is devoted the analysis of the reasons of occurrence of legal system of the European Community and its subsequent adaptation in the European Union. The basic attention is given to research of system of sources of the right of EU. Efficiency of modern integration process depends on unification of legal system of the European Union. As integration in the long term will lead to involving in this process more and more spheres of public life of EU member states.